Village Head Communication Strategy in Disseminating Information and Services in the Hamparan Perak Pilot Village - Ghazali, Muhammad; Simamora, Irma Yusriani (UNIVERSITAS PAKUAN, 2023)
Communication Strategy is essentially a planning and management to achieve a goal. However, to achieve these goals, the strategy does not function as a road map that only shows direction, but must be able to show how operational steps to obtain the expected results. This research is a type of qualitative research that aims to describe the communication strategy of the head of hamparan perak village in disseminating information on pilot village services and to find out how obstacles are experienced by the village head in socializing the program. The results of this study show that the strategies carried out by the Head of Hamparan Perak Village in Socializing the Pilot Village Program include: 1) Determining the Objectives of the Information Receiving Object; 2) Conducting Persuasive Techniques in providing information on Pilot Villages and 3) Building Educational Communication. In socializing the pilot village program to the community, the Head of Hamparan Perak Village also experienced several obstacles including: 1) Obstacles in the delivery process, This happened because the Village Head had difficulty in conveying messages to the community who incidentally did not have a broad understanding of the pilot village; 2) Physical obstruction, this can be caused by, for example, poor hearing and disturbances in the system and disturbances in the system loudspeakers (sound system); 3) Social Barriers, this occurs because of the high selfishness of the people who are still attached to them as if they are able to live without the presence of the government.